Krzysztof Amielańczyk, Rzymskie prawo karne w reskryptach cesarza Hadriana, Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, Lublin 2006, ss. 289 - Zabłocki, Jan (Zeszyty Prawnicze, 2017)
Krzysztof Amielańczyk, Rzymskie prawo karne w reskryptach cesarza Hadriana, Wydawnictwo Uniwersytetu Marii Curie-Skłodowskiej, Lublin 2006, ss. 289